Community mental health doulas (CMHD): a novel approach to addressing mental health challenges in America (Journal of Ideas in Health, 2024)
Background: Mental health challenges in the United States persist, with significant disparities in access to care and outcomes. The Community Mental Health Doulas (CMHD) model emerges as a novel approach to address these issues by providing community-based, culturally competent support.Methods: A literature review was conducted, synthesizing research on doula care, community health workers, and mental health interventions published between 2018 and 2024.Results: The CMHD model shows promise in improving continuity of care, enhancing cultural competence, reducing stigma, and increasing community engagement. Implementation considerations include sustainable funding, ethical boundaries, collaboration with existing providers, and technology use. Challenges include potential resistance from traditional providers and ensuring quality across diverse communities.Conclusion: The CMHD model represents a transformative approach to addressing mental health challenges. While further research and pilot studies are needed, it holds significant potential to improve outcomes and reduce disparities. Future efforts should focus on evaluating long-term impacts and advocating for integration into mainstream mental health services.
Keywords: Community Mental Health, Doula Support, Cultural Competence, Mental Health Disparities, Integrated Care Model, United States of America